Enhanced AMPA receptor activity increases operant alcohol self‐administration and cue‐induced reinstatement. (6th November 2012) - Cannady, Reginald; Fisher, Kristen R.; Durant, Brandon; Besheer, Joyce; Hodge, Clyde W.
Abstract Long‐term alcohol exposure produces neuroadaptations that contribute to the progression of alcohol abuse disorders. Chronic alcohol consumption results in strengthened excitatory neurotransmission and increased α‐amino‐3‐hydroxyl‐5‐methyl‐4‐isoxazole‐propionate receptors (AMPA) receptor signaling in animal models. However, the mechanistic role of enhanced AMPA receptor activity in alcohol‐reinforcement and alcohol‐seeking behavior remains unclear. This study examined the role of enhanced AMPA receptor function using the selective positive allosteric modulator, aniracetam, in modulating operant alcohol self‐administration and cue‐induced reinstatement. Male alcohol‐preferring (P‐) rats, trained to self‐administer alcohol (15%, v/v) versus water were pre‐treated with aniracetam to assess effects on maintenance of alcohol self‐administration. To determine reinforcer specificity, P‐rats were trained to self‐administer sucrose (0.8%, w/v) versus water, and effects of aniracetam were tested. The role of aniracetam in modulating relapse of alcohol‐seeking was assessed using a response contingent cue‐induced reinstatement procedure in P‐rats trained to self‐administer 15% alcohol. Aniracetam pre‐treatment significantly increased alcohol‐reinforced responses relative to vehicle treatment. This increase was not attributed to aniracetam‐induced hyperactivity as aniracetam pre‐treatment did not alter locomotor activity. AMPA receptor involvement was confirmed because 6, 7‐dinitroquinoxaline‐2, 3‐dione (AMPA receptor antagonist) blocked the aniracetam‐induced increase in alcohol self‐administration. Aniracetam did not alter sucrose‐reinforced responses in sucrose‐trained P‐rats, suggesting that enhanced AMPA receptor activity is selective in modulating the reinforcing function of alcohol. Finally, aniracetam pre‐treatment potentiated cue‐induced reinstatement of alcohol‐seeking behavior versus vehicle‐treated P‐rats. These data suggest that enhanced glutamate activity at AMPA receptors may be key in facilitating alcohol consumption and seeking behavior, which could ultimately contribute to the development of alcohol abuse disorders.